Revisiting Vesicourethral Anastomosis during Open Radical Retropubic Prostatectomy; A Simple and Reproducible Technique: A Single Center Experience with 200 Cases - Basiri, Abbas; Hosseini Sharifi, Seyed Hossein (Urology Journal, 2019)
Purpose: Vesicourethral anastomosis (VUA) represents a challenging step of open radical prostatectomy (ORP) because of limitation of space in the depth of male pelvis, lack of control on knots during tightening which subsequently causes inadequate coupling of VUA or breakdown of knots, and also extremely difficult reapplication of sutures. To facilitate this step of ORP, we have developed a simple and reproducible technique and reported our 8-year experience. Materials and Methods: We used two extra-long DeBakey tissue forceps to approximate the bladder neck to the urethral stump. We found it more beneficial than Babcock clamp especially in obese patients with excess fatty tissue in the pelvic area. In this technique, the surgeon's assistant creates more space for the surgeon’s hand by sweeping the fatty tissue away from the anastomotic area and then pushes the reconstructed bladder neck down while the sutures are being tied. Results: We analyzed data from 200 patients with prostatic cancer who underwent open radical prostatectomy performed from 2009 to 2017. There were only 2 sutures disrupted during knot tying. In two cases (1%), drain output was more than 30 mL/day on postoperative day 2 and drainage was left in place for a longer duration. With the help of medications, time voiding and dedicated pelvic floor exercise whenever needed,.the goal of full urinary continence (0- 1 pad/day) was achieved in 85%, 94% and 98% of patients immediately after catheter removal, 3 months and 6 months after surgery, respectively. Eight patients (4%) developed urethral stricture. Conclusion: The surgical technique has been shown to be an independent predictor of urinary continence. We introduce a new simple modification of vesicourethral anastomosis during RP. Using this technique; in addition to reducing anastomotic disruption rate and increasing knot tying control, postoperative urinary continence after ORP may also be improved.